Establishment and verification of a contact model of flowing fresh concrete. Issue 7 (15th October 2018) - Zhao, Yuan; Han, Zhennan; Ma, Yali; Zhang, Qianqian
Abstract : Purpose: The purpose of this paper is to establish a new dynamic coupled discrete-element contact model used for investigating fresh concrete with different grades and different motion states, and demonstrate its correctness and reliability according to the rheological property results of flow fresh concrete in different working states through simulating the slump process and mixing process. Design/methodology/approach: To accurately express the motion and force of flowing fresh concrete in different working states from numerical analysis, a dynamic coupled discrete-element contact model is proposed for fresh concrete of varying strength. The fluid-like fresh concrete is modelled as a two-phase fluid consisting of mortar and aggregate. Depending on the contact forms of the aggregate and mortar, the model is of one of the five types, namely, Hertz–Mindlin, pendular LB contact, funicular mucous contact, capillary LB contact or slurry lift/drag contact. Findings: To verify the accuracy of this contact model, concrete slump and cross-vane rheometer tests are simulated using the traditional LB model and dynamic coupled contact model, for five concrete strengths. Finally, by comparing the simulation results from the two different contact models with experimental data, it is found that those from the proposed contact model are closer to the experimental data. Practical implications: This contact model could be used to address issues such as (a) the mixing, transportation and pumping of fresh concrete, (b) deeper research and discussion on the influence of fresh concrete on the dynamic performance of agitated-transport vehicles, (c) the behaviour of fresh concrete in mixing tanks and (d) the abrasion of concrete pumping pipes. Originality/value: To accurately express the motion and force of flowing fresh concrete in different working states from numerical analysis, a dynamic coupled discrete-element contact model is proposed for fresh concrete of varying strength.